2004
DOI: 10.1016/j.mod.2004.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Mutations affecting thymus organogenesis in Medaka, Oryzias latipes

Abstract: The thymus is an organ for T lymphocyte maturation and is indispensable for the establishment of a highly developed immune system in vertebrates. In order to genetically dissect thymus organogenesis, we carried out a large-scale mutagenesis screening for Medaka mutations affecting recombination activating gene 1 (rag1) expression in the developing thymus. We identified 24 mutations, defining at least 13 genes, which led to a marked reduction of rag1 expression in the thymus. As thymus development depends on ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 42 publications
(50 reference statements)
1
44
0
Order By: Relevance
“…Thymic rag1 expression in medaka is located bilaterally in the pharyngeal region and is detectable as early as stage 30 (3.5 dpf) [14,22,26]. We found that thymic rag1 expression was completely undetectable in every embryo of awb and awc mutants, whereas it was undetectable only in approximately half of the embryos of hjc embryos and was apparently reduced but slightly detectable in the other half [14] (Fig. 1A).…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…Thymic rag1 expression in medaka is located bilaterally in the pharyngeal region and is detectable as early as stage 30 (3.5 dpf) [14,22,26]. We found that thymic rag1 expression was completely undetectable in every embryo of awb and awc mutants, whereas it was undetectable only in approximately half of the embryos of hjc embryos and was apparently reduced but slightly detectable in the other half [14] (Fig. 1A).…”
Section: Resultsmentioning
confidence: 69%
“…Thymus development is differently defective in awabancha, awacha, and houjicha mutants We previously established awabancha (awb), awacha (awc), and houjicha (hjc) lines of medaka by screening for ethylnitrosoureainduced recessive mutations that affected immature-lymphocytespecific rag1 expression in the developing thymus [14]. Thymic rag1 expression in medaka is located bilaterally in the pharyngeal region and is detectable as early as stage 30 (3.5 dpf) [14,22,26].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations